MWNT/Cellulose Based Nanocomposite Electrodes for Ultrafast Flexible Li‐Ion Battery. Issue 1 (18th December 2017) - Tripathi, Balram; Srivastava, Nisha; Sharma, K. B.; Zagorskiy, Dmitri; Katiyar, Ram S.
Abstract : In the present study multiwall carbon nanotube (MWNT)/Ethyl cellulose (EC) based nanocomposite electrodes have been fabricated and tested for Li‐ion batteries. The insertion of MWNTs of high surface area (140 cm 2 ) in ethyl cellulose (EC) polymer has been implicated to obtain flexible and sufficient capacity electrodes. X‐ray diffraction spectra showing enhanced crystallinity, Raman spectra showing well orientation of MWNTs in composites, scanning electron microscopy (SEM) images showing MWNTs dominance on surface of the composites, Fourier transform infrared (FT‐IR) spectroscopy confirms interfacial interactions and charging‐discharging profiles showing enhanced and stable charge storage capacity of composite electrodes. The electrodes of MWNT/EC nanocomposite exhibit charge capacities in between 70–240 mAh/g at charging rate (C/10). These nanocomposite electrodes can be charged up to current of 50 mA/cm 2 with only 5% loss in capacity over 50 subsequent charge and discharge cycles. These composite electrodes are flexible, ultra fast and lightweight.